A Pan-STARRS1 Search for Substellar Young Moving Group Members. Issue Volume 10:Issue S314(2015) (November 2015) - Aller, Kimberly M.; Liu, Michael C.; Magnier, Eugene A.
Abstract: Young moving groups (YMGs) are coeval, comoving groups of stars which have migrated from their birthsites after formation. In the substellar regime, YMG members are key benchmarks to empirically define brown dwarf evolution with age and to study the lowest mass end of the initial mass function. We have combined Pan-STARRS1 (PS1) proper motions with optical+IR photometry from PS1, 2MASS and WISE to perform a large-scale (≈30, 000 deg 2 ) systematic search for substellar members down to ≈10 MJup . We have obtained near-IR spectroscopy of a large sample of ultracool candidate YMG members to assess their youth via gravity-sensitive absorption features. We have identified several new intermediate-gravity candidate members of the AB Dor Moving Group, potentially greatly expanding the substellar membership. These new candidate members bridge the gap between the known low-mass stellar and planetary-mass members and yield valuable insight into the spectral characteristics of young brown dwarfs.